2019
DOI: 10.1016/j.cgh.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Use of Nonalcoholic Fatty Liver Disease Fibrosis Score, Fibrosis-4 Score, and Liver Stiffness Measurement to Identify Patients With Advanced Fibrosis

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e147. Learning Objective-Upon completion of this activity, successful learners will be able to apply the use of noninvasive fibrosis score and liver stiffness measurement for evaluation of advanced fibrosis in patients with nonalcoholic fatty liver disease. BACKGROUND & AIMS: Measuring liver stiffness only in patients with indeterminate or high nonalcoholic fatty liver disease (NAFLD) fibrosis scores (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 20 publications
0
95
0
Order By: Relevance
“…Alternatively, one may perform another noninvasive test to gain more information. (26,27) With regard to CAP changes, 52.0% of patients showed an increased CAP suggestive of new NAFLD development and 12.2% had a CAP that decreased to <248 dB/m at the 3-year follow-up. Previous studies using oral glucose tolerance tests showed that insulin resistance was almost universal in patients with NAFLD, highlighting the close relationship between NAFLD and prediabetes and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, one may perform another noninvasive test to gain more information. (26,27) With regard to CAP changes, 52.0% of patients showed an increased CAP suggestive of new NAFLD development and 12.2% had a CAP that decreased to <248 dB/m at the 3-year follow-up. Previous studies using oral glucose tolerance tests showed that insulin resistance was almost universal in patients with NAFLD, highlighting the close relationship between NAFLD and prediabetes and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…+++++AUC ≥0.90, ++++AUC 0.85–0.89, +++AUC 0.80–0.84, ++AUC 0.75–0.79, +AUC <0.75 (Harrell’s c index substituted for AUC for prognostic category).*Accuracy for determining advanced (bridging) fibrosis abstracted from meta-analyses where available7 9 12 118 or from large cohorts of chronic liver disease patients 26 59 74 119–123†Proportion of cases falling within an indeterminate range for the prediction of advanced fibrosis 6 38 72 119 120 124–127‡AUC for significant (F2-4) fibrosis.ALD, alcoholic liver disease; ALT, alanine aminotransferase; Apo-A1, apolipoprotein-A1; APRI, AST-Platelet Ratio Index; AST, aspartate aminotransferase; AUC, area under the curve; BMI, body mass index; CHB, Chronic hepatitis B; CHC, chronic hepatitis C; HA, hyaluranic acid; IFG, impaired fasting glucose; α2-M, α2-macroglobulin; NA, not applicable; NAFLD, non-alcoholic fatty liver disease; PNPIII, procollagen N-terminal peptide III; PSC, primary sclerosing cholangitis; PTI, prothrombin index; TIMP-1, tissue inhibitor of matrix metalloproteinase-1.…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
“…†Proportion of cases falling within an indeterminate range for the prediction of advanced fibrosis 6 38 72 119 120 124–127…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
“…It should be kept in mind that FIB‐4 and NFS do not adequately rule‐in advanced fibrosis (with a high rate of false‐positive results), thus further assessment with a more specific test is required in case of positive results. Several tests have been proposed for these cases, including ELF TM , Fibrometer® and TE . For instance, in a large, prospective study of a UK primary care referral pathway in 1,452 patients with NAFLD, Srivastava et al recently showed that a two‐step pathway (FIB‐4 followed by ELF TM performed in those with an indeterminate (score 1.3‐3.25) FIB‐4) reduced unnecessary referrals to liver specialists by 81%, and also markedly increased (five‐fold) the accurate referral of cases with advanced fibrosis.…”
Section: Referral Pathways From Primary Healthcare/diabetes Clinics Tmentioning
confidence: 99%
“…Several tests have been proposed for these cases, including ELF TM , 24,25 Fibrometer® 26 and TE. 23,[25][26][27] For instance, in a large, prospective study of a UK primary care referral pathway in 1,452 patients with NAFLD, Srivastava et al 24 recently showed that a two-step pathway (FIB-4 followed by ELF TM performed in those with an indeterminate (score 1.3-3.25) FIB-4) reduced unnecessary referrals to liver specialists by 81%, and also markedly increased (five-fold) the accurate referral of cases with advanced fibrosis. Importantly, because of the dual FIB-4 or NFS cut-offs, a significant proportion of patients (around 30%) fall in the intermediate risk category and cannot be correctly classified (indeterminate results).…”
Section: Primary Healthcarementioning
confidence: 99%